The Influence of Human Capital, use of Information Technology, and Internal Control on the Quality of Financial Reports at BPR in Denpasar - ANGELIN, Komang Ratu Karina; ASTUTI, Partiwi Dwi; ANGGIRIAWAN, Putu Budi (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to test the influence of human capital empirically, the use of information technology, and internal control on the quality of financial reports. The sample used in this research was saturated, namely 30 BPRs with addresses in Denpasar. This research data is quantitative and was collected using a questionnaire. The analysis technique used is the multiple linear regression analysis technique. The results of this research are that human capital has a positive and significant effect on the quality of financial reports, the use of information technology has a positive and significant effect on the quality of financial reports, and internal control has a positive and significant effect on the quality of financial reports. In addition, this provides implications for future researchers to add other variables such as internal audit, accounting information systems, and others. It is necessary to increase the number of samples and expand the scope of research, which is more comprehensive than BPR in Denpasar.